Diagnóstico de Conflicto entre los contextos de Trabajo y Familia en el Área de Supervisión, Perteneciente a una Empresa Orientada al Servicio de Construcción en el Ámbito Petrolero, con Jornadas Laborales Excepcionales - Zambrano Cisneros, Carolina Elizabeth (2014)
The purpose of this search is to determine the frequency of conflict within the context work-family in the field of supervision, in a company aimed at building services in the petroleum area with exceptional longer journals. With this work is paying attention how family and work are issues related, its influence and the quality of relation existing between both.m In addition, It was used a quantitative design with a descriptive focus, considering a universal sample of 78 people. In order to comply with the objectives, it was collected the data through an instrument called SWING “Interaction Questionnaire Work -Family”, which was structured to measure the positive interaction between work-family and negative interaction work-family. Positive interaction family-work and negative interaction family-work...